2016
DOI: 10.1104/pp.16.00647
|View full text |Cite
|
Sign up to set email alerts
|

The Low Molecular Weight Protein PsaI Stabilizes the Light-Harvesting Complex II Docking Site of Photosystem I

Abstract: PsaI represents one of three low molecular weight peptides of PSI. Targeted inactivation of the plastid PsaI gene in Nicotiana tabacum has no measurable effect on photosynthetic electron transport around PSI or on accumulation of proteins involved in photosynthesis. Instead, the lack of PsaI destabilizes the association of PsaL and PsaH to PSI, both forming the light-harvesting complex (LHC)II docking site of PSI. These alterations at the LHCII binding site surprisingly did not prevent state transition but led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 89 publications
0
9
0
1
Order By: Relevance
“…The PsaI protein stabilises PsaL in the cyanobacterium Synechocystis 39 ; PsaL and PsaH form a docking site for light-harvesting complex II (LHCII) during state transitions in tobacco 40 and the stability of this site relies on PsaI 41 . PsaI is present in all taxa considered here except for Chromera , Vitrella , Aureococcus , and the secondary green algae Bigelowiella natans and Euglena gracilis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PsaI protein stabilises PsaL in the cyanobacterium Synechocystis 39 ; PsaL and PsaH form a docking site for light-harvesting complex II (LHCII) during state transitions in tobacco 40 and the stability of this site relies on PsaI 41 . PsaI is present in all taxa considered here except for Chromera , Vitrella , Aureococcus , and the secondary green algae Bigelowiella natans and Euglena gracilis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thylakoid membranes were isolated as described previously ( Schöttler et al , 2004 ). The chlorophyll content and a/b ratio were determined in 80% (v/v) acetone according to Porra et al (1989) . The contents of PSII and the b 6 f were determined from difference absorbance signals of cytochrome b 559 (PSII) and the cytochromes b 6 and f in destacked thylakoids equivalent to 50 µg chlorophyll mL −1 ( Kirchhoff et al , 2002 ).…”
Section: Methodsmentioning
confidence: 99%
“…These findings yielded further insights into the reorganization of supercomplexes associated with state transitions, and it was suggested that phosphorylation of LHCB2 rather than LHCB1 is the essential trigger for the formation of state transition supercomplexes (Leoni et al, 2013;Pietrzykowska et al, 2014;Crepin and Caffarri, 2015;Longoni et al, 2015). Furthermore, characterization of mutants deficient in individual PSI core subunits indicates that PsaH, L, and I are required for docking of LHCII at PSI (Lunde et al, 2000;Zhang and Scheller, 2004;Kouril et al, 2005;Plöchinger et al, 2016).…”
mentioning
confidence: 99%